(untitled) (Al-Academy, 2016)
Find goal to detect educational and technical staffing of style fiction in book reading school materials so determine the current research on the specific book reading in fourth grade of primary for the academic year 2014 issued by the Ministry of Education / Republic Iraq stories. Come in the importance of research to draw attention to the best of these stories and strengthened, and the negative deny it and claim his deportation in order to protect the thought of the learner, and the study may contribute to the development of some frameworks to write a story appropriate for elementary school. This McCann within the first chapter The second chapter included the theoretical framework has been contained on two main sections included the concept of values, and the importance of values, and classification of the educational role of the style of fiction and its relationship to values, and the story of education and its role, and the types of educational stories. And benefited researcher than offered from previous studies and the most important outcome of the theoretical framework in the third quarter research procedures have been used descriptive analytical method, which is based on the method content analysis and the research community, which included stories in a book reading for fourth grade and the 24 story, and identified research sample (5) of these stories were chosen at random a regular basis, and then prepare the search tool and persistence and sincerity computational and statistical methods used . the fourth quarter was the presentation and discussion of results, and it was the most important conclusions that the educational and technical employment played a key role in the formulation of the foundations of intellectual-oriented learner through treatment technical studied in its use of words short and simple phrases that understood by the learner and absorbed and then can be reflected in his daily life with a discrepancy in the stories between the consensus for the title of the story with the content of their non-compliance, and came out with recommendations, and proposals and finally the list of sources and references